2017
DOI: 10.3389/fphar.2017.00259
|View full text |Cite
|
Sign up to set email alerts
|

Inverted U-Shaped Dose-Response Curve of the Anxiolytic Effect of Cannabidiol during Public Speaking in Real Life

Abstract: The purpose of this study was to investigate whether the anxiolytic effect of cannabidiol (CBD) in humans follows the same pattern of an inverted U-shaped dose-effect curve observed in many animal studies. Sixty healthy subjects of both sexes aged between 18 and 35 years were randomly assigned to five groups that received placebo, clonazepam (1 mg), and CBD (100, 300, and 900 mg). The subjects were underwent a test of public speaking in a real situation (TPSRS) where each subject had to speak in front of a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
3
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(229 citation statements)
references
References 55 publications
10
194
3
10
Order By: Relevance
“…CBD also reduced anxiety induced by simulated public speaking in both healthy volunteers and patientswith social anxiety disorders [32,33]. Consistent with animal studies, acute administration of CBD induced anxiolytic effects in healthy subjects with moderate (300 mg), but not lower (100 mg) or higher (900 mg) doses [34]. CBD can also attenuate anxiety related sleep problems.…”
Section: Anxiolytic Effect Of Cbdsupporting
confidence: 61%
“…CBD also reduced anxiety induced by simulated public speaking in both healthy volunteers and patientswith social anxiety disorders [32,33]. Consistent with animal studies, acute administration of CBD induced anxiolytic effects in healthy subjects with moderate (300 mg), but not lower (100 mg) or higher (900 mg) doses [34]. CBD can also attenuate anxiety related sleep problems.…”
Section: Anxiolytic Effect Of Cbdsupporting
confidence: 61%
“…In another study (Guimarães et al, 1987), lorazepam (1mg) decreased subjective ratings of anxiety, but tended to increase HR responses to stress. Lastly, Zuardi et al (2017) found that clonazepam (1 mg) decreased ratings of anxiety during and after a public speaking task, but increased HR response to the stress.…”
Section: Introductionmentioning
confidence: 91%
“…CBD did not alter cardiovascular function, and cortisol was not measured. In a second study, Zuardi et al (2017) compared effects of several doses of CBD (100 mg, 300 mg, 900 mg) using a variant of a public speaking task in which 12 participants were tested at once. They found a nonlinear dose-response function such that only the moderate dose (300 mg) reduced ratings of anxiety during and after a public speaking task, despite slightly increasing BP during the task.…”
Section: Introductionmentioning
confidence: 99%
“…In der Phase nach der Rede (3,5 h nach Einnahme) zeigten Clonazepam und 300 mg CBD eine angstlösende Wirkung -nicht aber 100 mg und 900 mg CBD [10]. 24 Patienten mit sozialen Angststörungen wurden in einer Doppelblindstudie mit 600 mg CBD oder Placebo behandelt: CBD zeigte eine signifikante vermindernde Wirkung bei der subjektiven Beurteilung der Angst und der kognitiven Beeinträchtigung [11].…”
Section: Anxiolytische Wirkungunclassified
“…In einer grösseren Studie konnte dies für 300 mg -nicht aber für 100 und 900 mg -bestätigt werden [10]. Die klinische Relevanz dieser Erkenntnis ist noch offen.…”
Section: Diskussionunclassified